Verification for the control of kappa-casein gene on milk protein yield of friesian-holstein in dairy central region of West Java - A. Anggraeni; C. Sumantri; A. Farajallah; E. Andreas (Jurnal Ilmu Ternak dan Veteriner, 2009)
Genotipe of BB kappa kasein (ĸ-kasein) gene positively influences high milk protein yield. The aim of this research was to verify the use of the к-casein gene as marker of assisted selecion (MAS) of high protein yield in domestic Holstein-Friesian (HF) cattle. Genotyping blood samples was conducted for lactating cows from BPPT-SP Cikole (82 head) and a number of small holders in KPSBU Lembang (190 head). Genotyping the к-casein gene was also conducted for active and non active AI bulls (HF) from BIB Lembang (25 head) and BBIB Singosari (32 head). Varian genotipes were identified trough DNA migration, whereas frequencies of alleles were calculated by Nei Method (1987). The effects of variant genotypes on protein yield and other milk component yields were studied in lactating cows (56 head in BPPT-SP Cikole and 111 head in KPSBU Lembang) by applying Least Square Means (LSM) method of the General Linear Model (GLM). Genotyping the ĸ-kasein gene resulted in three genotypes, namely AA, AB and BB, with two alleles, namely A and B. It was identified that a very limited number of lactating cows with BB genotype (0-9%). These cows produced higher protein yield around 3.37-3.84% than that of AA cows, while AB cows produced protein yield in between, though these differences were not statistically significant (P>0,05). In contrast, AA cows tended to produced higher milk fat yield than BB cows. Cows BB and AB seemingly produced higher dry matter, while both specific density and pH were not affected by variant genotypes of the к-casein gene.  The results showed that BB genotype of the к-casein gene tended to be quitely consistent in controlling high protein yield, so it would be a good oppurtinity to be used as MAS of milk protein yield in HF domestic. Key words: Protein Yield, Dairy Cattle (HF), к-Casein Gene, Genotype BB